2016
DOI: 10.1039/c6cc00457a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of high molecular weight polyethylene using iminopyridyl nickel catalysts

Abstract: A series of iminopyridyl Ni(ii) catalysts containing both the dibenzhydryl and the naphthyl moieties can polymerize ethylene with high activity and high thermal stability, generating polyethylene with a molecular weight of up to one million. In α-olefin polymerization, semicrystalline polymers with high melting temperatures are generated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
77
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(82 citation statements)
references
References 51 publications
(4 reference statements)
4
77
1
Order By: Relevance
“…brB 3 and brB 4 indicate the methine carbon of propyl and butyl branch, respectively. The resonances associated with butyl branches appear at 14.38 ppm (1B 4 ), 23.37 ppm (2B 4 ), and 37.56 ppm (brB 4 ), which correspond to the [EHE] sequence of ethylene (E) -1 -hexene (H) copolymer. [ 16,21 ] The resonances of propyl branches appear at 14.76 ppm (1B 3 ), 20.01 ppm (2B 3 ), and 36.29 ppm (3B 3 ), correspond to the [EAE] sequence of E -1 -pentene (A) copolymer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…brB 3 and brB 4 indicate the methine carbon of propyl and butyl branch, respectively. The resonances associated with butyl branches appear at 14.38 ppm (1B 4 ), 23.37 ppm (2B 4 ), and 37.56 ppm (brB 4 ), which correspond to the [EHE] sequence of ethylene (E) -1 -hexene (H) copolymer. [ 16,21 ] The resonances of propyl branches appear at 14.76 ppm (1B 3 ), 20.01 ppm (2B 3 ), and 36.29 ppm (3B 3 ), correspond to the [EAE] sequence of E -1 -pentene (A) copolymer.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5] In combination with a suitable cocatalyst, these complexes showed good activity for ethylene and 1 -alkene polymerizations, to produce highly Recently, Chen et al reported a series of iminopyridyl Ni(II) catalysts containing both the dibenzhydryl and the naphthyl moieties can polymerize ethylene with high activity and high thermal stability, and generated semicrystalline poly(1-alkene)s with high melting temperatures. [ 23 ] However, the polymerization of symmetrical monomer with longer alkyl chain has not been examined because of their very low reactivity toward polymerization catalysts. [ 10 ] If these monomers can polymerize easily to give high molecular weight polymers using an appropriate catalyst, they would become new polymer materials.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, our literature survey indicates that the phosphine-based nickel catalysts (III-VII) typically lead to the formation of highly linear polyethylenes in ethylene polymerization 24,25 . In contrast, most N^N-based or N^O-based nickel catalysts (I, II, and many others) generate variously branched polyethylenes [26][27][28][29][30][31][32] . Industrially, branches are introduced through α-olefin copolymerization to improve the processability as well as many other material properties of polyolefins.…”
mentioning
confidence: 99%
“…Complex 29, an iminopyridyl ligated catalyst developed by Chen and co-workers, was found to polymerize ethylene at 80 ∘ C with an activity of 16.8 × 10 5 g (mol Ni) −1 h −1 when activated using diethylaluminium chloride, albeit only achieving low molecular weights (M n = 21 kg mol -1 ). 74 Related iminopyridine-N-oxide catalyst 30 proved to be equally promising, displaying a polymerization activity of 1.9 × 10 6 g (mol Ni) −1 h −1 at 80 ∘ C, and achieving weight-average molecular weights (M w ) of 90 kg mol -1 . 75 Additionally, neutral Ni catalysts 31a and 31b 76 can also lend insight into the importance that ligand structure has on catalyst activity and stability (Fig.…”
Section: Other Ligand Structuresmentioning
confidence: 99%